PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA SMP MATERI TEKANAN HIDROSTATIS - Sri Wahyuni; Siti Nurjannah; Aris Singgih Budiarso (Pendidikan Fisika FKIP UNEJ, 2022)
The development of science and technology has caused a lot of disruption to every element, especially in the education sector which affects students' critical thinking levels. Science learning is one of the lessons that can provide direct experience so that it can improve students' critical thinking skills. In fact, the use of passive learning models also affects the low critical thinking skills of junior high school students. An alternative way that can be done is by selecting an efficient and effective learning model according to the student's condition. The right learning model uses the Problem Based Learning because it is able to guide students to solve problems and critical thinking skills so as to help students understand more deeply about a science phenomenom. This fact is the basis for research that aims to significantly examine the PBL model on students' critical thinking skills in learning hydrostatic pressure material. This type of research is a quasi-experimental design with a post-test only control group and two research samples were selected, namely the experimental class VIII and the control VIII class. Data collection is in the form of critical thinking skills tests. The results of this study are in accordance with the data analysis showing that the average post-test the experimental class is higher than the control class. The average of the experimental class is 75.3 while the average value of the control class is 61.6. The high average post-test in the experimental class indicates that the science learning of hydrostatic pressure material carried out using the PBL model has an effect on improving students' critical thinking skills.